ROLE OF CONVECTIVE BOUNDARY CONDITIONS ON MAGNETOHYDRODYNAMIC PHYSIOLOGICAL FLUID FLOW UNDER AN IMPACT OF RADIATION AND HALL CURRENT - S. Ravikumar; V. Nagaradhika; M. Ramanuja (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this investigates an analysis of convective boundary conditions on magneto hydrodynamic physiological fluid flow under an impact of radiation and hall current through tapered vertical channel with a porous medium. Analytical results are found for the velocity, pressure gradient, heat transfer coefficient and temperature. An influence of varied governing parameters were discussed and illustrated diagrammatically through a set of figures. It could be noticed that the velocity distribution reduces by increase in hall current parameter while it reduces when increase in biot number. Temperature distribution enhances by increase in radiation parameter while it reduces when increase in biot number.